The guidebook of Malaysian traditional cultural activities; wau, gasing and wayang kulit / Nik Nurul Iffah Nik Abdullah Zawawi - Nik Abdullah Zawawi, Nik Nurul Iffah (2022)
The purpose of this study is to focus on preserving the Malaysian traditional cultural activities that are based in Kelantan which are wau, gasing and wayang kulit. From this topic, a researcher needs to complete the study about raising awareness to conserve the heritage of Malay culture. A group's cultural history is unique, valuable, and incomparable. It is now up to today's youth to preserve culture for future generations. They must also adhere to the same traditions and etiquette. As a result, they will be able to avoid any changes to the cultural legacy during their lifetime. Maintaining the heritage alive helps to better the environment. It is widely acknowledged that keeping heritage assets give advantages to society. This study also consists of two research objectives of the study, the first objective is to identify the cultural activities from Kelantan and the second objective is to create a guidebook of cultural activities such as wau, gasing and wayang kulit by using illustration. The research questions of this study are what are the cultural activities that can be found in Kelantan and how the guidebook of cultural activities can be visualized? In order to gain the information for this research systematically, the primary data was collected by using the quantitative method by conducting a survey about the topic. There were 67 respondents that have filled out the questionnaire through Google Form. Furthermore, to obtain further information regarding the topic, the researcher has used secondary data such as books reference and internet resources. Throughout this study, the researchers encouraged that Malaysian need to sustain cultural activities from Malaysia to prevent the heritage from fading.